ANALISIS KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA PT BANK PERKREDITAN RAKYAT UTOMO MANUNGGAL SEJAHTERA SUMATERA SELATAN - Ngadi, Setiawan; Anwar, Yuniarti; Wiralaga, Harby R (STIE DWI SAKTI BATURAJA, 2024)
The purpose of this study was to determine the non-performing loans on profitability at PT Bank PerkreditanRakyat Utomo Manunggal Sejahtera, South Sumatra. The data analysis technique used in this study usedqualitative and quantitative analysis. The data obtained using the case study method through two types ofdata, namely primary data which is data obtained directly from data sources with direct observation ofsecondary data which is supporting data obtained from other sources or through other intermediariesrelated to research. Based on the results of calculations from the analysis of non-performing loans (NonPerforming Loans) on profitability as measured by Return On Assets and Return On Equity at PT Bank Perkreditan Rakyat Utomo Manunggal Sejahtera South Sumatra during 2016 to 2020 it can be concludedthat non-performing loans (Non Performing Loans)) has an effect on Return On Assets (ROA) and Return OnEquity (ROE). This is evidenced by the increase in the ratio of non-performing loans (Non Performing Loans)in 2018 by 0.01% (from NPL in 2017 of 0.25% to 0.26% in 2018), in 2019 an increase of 0.34% (from NPL in2018 was 0.26% to 0.60% in 2019) and 2020 increased by 0.64% (from NPL in 2019 of 0.60% to 1.24% in2020) which resulted in a decrease in the Return On ratio Assets (ROA) in 2018 was 0.01% (from ROA in 2017of 3.51% to 3.50% in 2018), in 2019 decreased by 1% (from ROA in 2018 of 3.50% to 2 .50% in 2019) and2020 decreased by 0.26% (from ROA in 2019 of 2.50% to 2.24% in 2020) and resulted in the Return OnEquity (ROE) ratio in 2018 decreasing by 1, 55% (from ROE in 2017 of 35.22% to 33.67% in 2018), in 2019decreased by 9.29% (from ROE in 2018 of 33.67% to 24.38% in 2019) and in 2020 decreased by 5.46% (da riROE in 2019 of 24.38% to 18.92% in 2020) which shows that the occurrence of non-performing loans (NonPerforming Loans) causes the profit obtained from the proceeds of asset funding to decrease because banksdo not get interest on loans disbursed, with If the profit is reduced then the amount of bank capital does notincrease because one of the components of capital is the bank's profit